(untitled) (Tokyo, 1936)
The original Japanese edition was published six years ago. About a quarter of the text was devoted to an outline of Western alchemy for the benefit of Japanese readers. In the English version that part has been omitted.
Keywords: Giả kim,Alchemy; Lịch sử,History